Relationship Between Patient-Centered Primary Care Provider Communication and Emergency Room Visits in the Medicaid Population in North Carolina, United States - Elena A. Platonova; Keith J. Carnes (SAGE Publishing, 2023)
Introduction: Medicaid, a joint federal-state program, finances health care for eligible low-income individuals and families in the United States. Medicaid patients use disproportionately more emergency room (ER) services than other patients in the United States. Inadequate provider communication during primary care visits might be one reason for this well-documented phenomenon. The goal of the study was to examine how patient-centered provider communication related to ER use by Medicaid patients in North Carolina. Methods: A 2015 state-wide cross-sectional telephone survey of NC adult Medicaid patients (n = 2652) was based on the CAHPS methodology. Predictors were 4 patient-centered provider communication characteristics assessed by patients. The outcome was the number of ER visits during 6 months prior to the survey. We used negative binomial regression to examine the relationship. Results: Effective patient-centered provider communication index was associated with 19% fewer ER visits ( P  < .05). Provider's respect for patients had the biggest impact on the number of visits (37% fewer ER visits, P  < .001). Easy to understand provider explanations were associated with 18% fewer ER visits ( P  < .05). Longer (>1 year) patient continuity with the current primary care provider was associated with 36% to 38% fewer ER visits ( P  < .001). Conclusions: Health care quality improvement should focus on training providers how to show respect, give easily understood explanations, and maintain good interpersonal relationships with patients. Relevant agencies should emphasize training and accreditation with a specific emphasis on communication of providers delivering care to Medicaid patients.